2020
DOI: 10.1186/s12935-020-01379-5
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation and microRNA-target regulation are associated with downregulated NEURL1B: a diagnostic and prognostic target in colon cancer

Abstract: Background Aberrant methylation and miRNA-target-gene regulation function as important mechanisms for gene inactivation in colon carcinogenesis. Although a serious of molecular events (such as aberrant alterations of genomics and epigenetics) have been identified to be related to prognostic in colon cancer (CC) patients, beneficial biomarkers for early diagnosis and prognostic evaluation remain largely unknown. Methods In our study, the role of NEURL1B, including gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Consistent with the significant downregulation of ARID1B expression in colon cell lines and TCGA tissues, ARID1B was hypermethylated in COAD tissues. Comparison of these findings with those of previous studies confirmed silenced expression of genes, especially ARID1B by aberrant methylation of DNA in cancer (Chuang and Jones, 2007;Khursheed et al, 2013;Liu et al, 2020;Tan et al, 2020). AKR1C2 mRNA, a gene previously identified as a Nrf2-target, was not found in HCT116 cells (Ebert et al, 2011).…”
Section: Figuresupporting
confidence: 74%
“…Consistent with the significant downregulation of ARID1B expression in colon cell lines and TCGA tissues, ARID1B was hypermethylated in COAD tissues. Comparison of these findings with those of previous studies confirmed silenced expression of genes, especially ARID1B by aberrant methylation of DNA in cancer (Chuang and Jones, 2007;Khursheed et al, 2013;Liu et al, 2020;Tan et al, 2020). AKR1C2 mRNA, a gene previously identified as a Nrf2-target, was not found in HCT116 cells (Ebert et al, 2011).…”
Section: Figuresupporting
confidence: 74%
“…Herein, using transcriptome, DNA methylation, and driver mutations of CRC, we developed a classifier based on multi-omics integration for the prognosis prediction of CRC for the first time. At present, many studies have proved that CRC is the result of accumulation of multiple gene mutations and epigenetic modifications, and DNA hypermethylation or hypomethylation can be used as epigenetic biomarkers to predict the occurrence and prognostic effects of CRC (75)(76)(77). Driver mutations in the genome can be viewed as responsible for molecular changes associated with CRC progression, so targeting such genes for the elimination of multiple CRC gene dependencies could significantly improve efficacy (78).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CENPA, we identified additional potential target genes of MYBL2 and FOXM1 in lung adenocarcinoma ( Figure 4 ). For example, neuralized E3 ubiquitin protein ligase 1B (NEURL1B) is known to act as a tumor suppressor gene in colon cancer and medulloblastoma [ 41 , 42 ]. However, in our study, we found that NEURL1B acts more like an oncogene in lung adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%